Pengaruh Pendekatan Pembelajaran Konstekstual Bermuatan Nilai Budaya Dan Karakter Bangsa Terhadap Hasil Belajar Ditinjau Dari Sikap Demokrasi Pada Pelajaran Pendidikan Kewarganegaraan - Ketut Bali Sastrawan; Komang Satya Permadi; Kadek Hengki Primayana (Purwadita : Jurnal Agama dan Budaya, 2021)
Character is a person's character, character, morals, or personality which is formed from the internalization of various virtues that are believed and used as a basis for perspective, think, behave, and act. Virtue consists of a number of values, morals, and norms, such as honesty, courage to act, trustworthiness, and respect for others. The interaction between one person and another fosters the character of the community and the character of the nation. Therefore, the development of the nation's character can only be done through the development of a person's individual character can only be done in the socio-cultural environment concerned. In other words, educating the culture and character of the nation is to develop Pancasila values in students through heart, brain and physical education. Education is a conscious and systematic effort in developing the potential of students. Education is also a society and a nation in preparing its young generation for the sustainability of the life of a better society and nation in the future.